(untitled) (Research, Society and Development, 2025)
Pig farming has significant economic importance in Brazil but still faces considerable challenges, especially regarding animal welfare in confinement systems. In these restricted environments, pigs often have their natural behavioral needs limited, which can lead to stress, aggression, and other behavioral disorders. In this context, environmental enrichment emerges as a viable and effective strategy to make the environment more stimulating and healthy for the animals. This study aimed to investigate, through a literature review, how different environmental enrichment strategies impact the behavior and welfare of pigs raised in confinement. Studies published between 1995 and 2025 were analyzed, seeking to identify practices that demonstrated the greatest effectiveness, as well as to discuss their benefits and limitations. The research provides a knowledge base to guide producers, technicians, and students on the practical application of these strategies, showing that environmental enrichment goes beyond regulatory compliance, functioning as a tool that promotes health, welfare, and sustainability in pig production. It is concluded that adopting environmental enrichment strategies, combined with proper management practices, is essential to promote pig welfare, reduce abnormal behaviors, and improve productive performance.